Pengaruh Fee Audit, Ukuran Kap, Spesialisasi Auditor, dan Workload Terhadap Kualitas Audit - Kartika Setyowati; Fatchan Achyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of audit fees, audit firm size, auditor specialization, and workload on audit quality in companies listed on the LQ45 Index of the Indonesia Stock Exchange for the 2020-2022 period. A quantitative research method using secondary data from annual financial reports was employed. The sample was determined using purposive sampling based on specific criteria. The dependent variable is audit quality, measured using an earnings benchmark with Return on Assets (ROA) as a proxy. Independent variables include audit fees (natural logarithm), audit firm size (Big 4 and non-Big 4), auditor specialization (specialization percentage), and workload (Audit Capacity Stress). Data were analyzed using logistic regression with a 5% significance level. The results indicate that audit fees, audit firm size, auditor specialization, and workload do not significantly affect audit quality. The study's limitations include the use of a sample limited to LQ45 companies over three years and the inclusion of only four independent variables. Future research is recommended to include additional variables such as audit tenure, client pressure, and auditor reputation to improve the model.